2007
DOI: 10.1021/ma071440e
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of the Confining Forces Imposed on a Single Molecule in a Concentrated Solution of Circular Polymers

Abstract: We measure the forces confining the displacement of a single DNA molecule embedded within a concentrated solution of long relaxed circular DNA molecules (115 kbp at 1 mg/mL) using optical tweezers. We compare these measurements with our previous measurements of forces imposed by entangled linear DNA molecules of the same length and concentration. A tube-like confining field and three relaxation modes were observed, but the tube radius was 25% smaller (=0.6 µm) and the longest relaxation time ∼3 times shorter (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 48 publications
4
31
0
Order By: Relevance
“…Similar experiments carried out for entangled ring DNA of the same length and concentration showed that the tube radius a C was ~25% smaller than that for linear DNA ( a C ≅ 0.75 a L ≅ 0.6 µm), and the confinement field was weaker, displaying a subharmonic dependence on displacement [ 84 ]. The measured tube radius was close to predictions based on the pom–pom ring (PPR) model that applies the pom–pom model concept of lattice-tree polymer configurations, originally developed for branched polymers, to entangled rings [ 49 ].…”
Section: Single-molecule Manipulationmentioning
confidence: 95%
“…Similar experiments carried out for entangled ring DNA of the same length and concentration showed that the tube radius a C was ~25% smaller than that for linear DNA ( a C ≅ 0.75 a L ≅ 0.6 µm), and the confinement field was weaker, displaying a subharmonic dependence on displacement [ 84 ]. The measured tube radius was close to predictions based on the pom–pom ring (PPR) model that applies the pom–pom model concept of lattice-tree polymer configurations, originally developed for branched polymers, to entangled rings [ 49 ].…”
Section: Single-molecule Manipulationmentioning
confidence: 95%
“…It is considered that chain uncrossability is better demonstrated by experiments with ring polymers since only they are capable of forming mathematically rigourous topological ''knots'' with neighbouring chains that permanently prevent chain crossing. [34] However, direct measurement of confining forces in concentrated solutions of linear and circular polymers demonstrate that the confining force imposed by circular polymers was substantially lower and of shorter range than that measured with linear polymers. [34] Based on these results, it was concluded that circular chains are less effective than linear chains at producing restrictive entanglements.…”
Section: à9mentioning
confidence: 96%
“…[34] However, direct measurement of confining forces in concentrated solutions of linear and circular polymers demonstrate that the confining force imposed by circular polymers was substantially lower and of shorter range than that measured with linear polymers. [34] Based on these results, it was concluded that circular chains are less effective than linear chains at producing restrictive entanglements. Still another demonstration that the looping picture and binary contacts between polymer chains cannot explain the elastic properties of polymer melts was obtained with experiments performed with entangled, non-concatenated, ring polystyrenes.…”
Section: à9mentioning
confidence: 96%
“…Here, it is important to note that c * is defined under equilibrium conditions when the linear polymers are unstretched by flow. Moreover, ring polymers generally exhibit a markedly different molecular weight dependence of the center-of-mass diffusion coefficient compared to linear polymers in background solutions of concentrated linear polymers or melts 19,20 . Nevertheless, it is possible to use single ring polymers as tracer polymers or probes to study entangled linear chain dynamics through small angle neutron scattering (SANS) or neutron spin echo (NSE) spectroscopy 21,22 , essentially by taking advantage of the slow diffusion of rings in ring-linear blends.…”
Section: Introductionmentioning
confidence: 99%